Contact transition control by adjusting emitting energy of proximity sensor. (17th January 2021) - Arita, H.; Suzuki, Y.
ABSTRACT: This paper proposes a control method to handle a state transition between a non-contact state and a contact state. The method is based on only force control instead of switching strategy between position control and force control. The main idea of the method is to utilize outputs of reflective proximity sensors as virtual forces and change the emitting energy of the sensors to adjust the magnitudes of the forces. The virtual force works as if the robot is covered with virtual elastic skin, the thickness of which relates to the magnitude. To evaluate the effectiveness, we conducted experiments with a simple robot arm, which has 1 degree of freedom and has an original proximity sensor specialized for the arm's shape. The results showed that the contact force became the desired value when the emitting energy equaled zero regardless of the speed of the transition, reflectance of the object, and whether the object is moving. The results, furthermore, indicated the method could control the contact force during the transition regardless of the difference of the contact point if the reflectance could be estimated. We concluded from these results that the proposed method is useful to control the transition. GRAPHICAL ABSTRACT: UF0001